2022
DOI: 10.1111/1541-4337.12999
|View full text |Cite
|
Sign up to set email alerts
|

Flavor of tea (Camellia sinensis): A review on odorants and analytical techniques

Abstract: Tea is among the most consumed nonalcoholic beverages worldwide. Understanding tea flavor, in terms of both sensory aspects and chemical properties, is essential for manufacturers and consumers to maintain high quality of tea products and to correctly distinguish acceptable or unacceptable products. This article gives a comprehensive review on the aroma and off-flavor characteristics associated with 184 odorants. Although many efforts have been made toward the characterization of flavor compounds in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(72 citation statements)
references
References 200 publications
0
72
0
Order By: Relevance
“…Theanine, a free amino acid only abundant in C. sinensis, is an odorless precursor participated in the formation of pyrazines during tea processing. , A variety of parameters including time, pH, temperature, water, and enzymes play key roles in the formation of pyrazines. , Trimethylpyrazine can be generated by heating glycine-sucrose and L -ascorbic acid-glycine model systems, or L -serine and -threonine alone, and it was the main product of the above Maillard reactions. 2-Ethyl-3,5-dimethylpyrazine can be generated via thermal treatment in the d -glucose and alanine model system, , or L -threonine .…”
Section: Resultsmentioning
confidence: 99%
“…Theanine, a free amino acid only abundant in C. sinensis, is an odorless precursor participated in the formation of pyrazines during tea processing. , A variety of parameters including time, pH, temperature, water, and enzymes play key roles in the formation of pyrazines. , Trimethylpyrazine can be generated by heating glycine-sucrose and L -ascorbic acid-glycine model systems, or L -serine and -threonine alone, and it was the main product of the above Maillard reactions. 2-Ethyl-3,5-dimethylpyrazine can be generated via thermal treatment in the d -glucose and alanine model system, , or L -threonine .…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our results, Joshi, Babu and Gulati [ 24 ] found that octanal and limonene were removed in green tea after the SCD. trans,trans-2,4-Heptadienal, methyl salicylate, β-cyclocitral, and safranal contributed to tea’s flower/fruit-like aroma, but they were hardly detected in green tea samples [ 30 ]. In our study, these volatile compounds were generated after decaffeination, indicating the potential aroma enrichment in DeCAF-GT.…”
Section: Resultsmentioning
confidence: 99%
“…Another study found that 2-ethyl-1-hexanol, (3Z)-3-hexen-1-yl hexanoate, and 2-pentylfuran were generated in green teas after the supercritical carbon dioxide decaffeination [ 31 ]. These results may be explained by the hydrolysis, volatilization, Maillard reaction, and redox reaction of aroma precursors, but the molecular mechanisms need to be revealed in further study [ 30 ]. The formation of β-cyclocitral and safranal may be due to the non-enzymatic degradation (auto-oxidation or thermal degradation) of carotenoids during tea processing [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…By comparing the intensities of the aroma-active compounds in WRTs with different cultivars, methyl octanoate (3.0−3.2), trans -linalool oxide (furanoid) (3.0−3.2), benzeneacetaldehyde (3.0−3.4), trans -β-ocimene (3.0−3.3), trans -alloocimene (3.2−3.4), 2-acetylpyrrole (3.0−3.2), and acetophenone (3.2−3.4) generally had strong aroma intensities (AI ≥ 3.0), but there were no significant differences among the samples, which may be due to the common and basic aroma-active components of WRTs. The above compounds also play important roles in the aroma formation of most kinds of teas, especially in black and oolong teas, which frequently present a typical floral scent [ 1 , 31 ]. Notably, some odorants, such as indole (1.0−2.5), methyl salicylate (2.4−3.3), 2,5-dimethylpyrazine (2.4−3.2), and p -cymene (2.0−3.2), had obvious gaps in the AI values among different WRTs.…”
Section: Resultsmentioning
confidence: 99%